Use of simulation practices in public or community health nursing: findings from mixed‐methods systematic review - Aslan, Funda (Scandinavian journal of caring sciences, 2021)
Background Simulation activities are valuable for nursing education and provide an experimental learning opportunity. However, simulation scenarios have focused on nursing education of traditional medical specialities, and limited research exists on simulation for community or public health nursing education. Aims This study aimed to explore the methods that are being used to increase the knowledge and skills of nursing students who work for public health nursing and the evidence about the effectiveness of simulation practices in public or community health nursing. Methods In this systematic review, a combination of keywords was selected from Medical Subject Headings based on which eight studies were found across Science Direct, Web of Science, EBSCO, Cochrane and PubMed databases between June 2018 and September 2018. Findings A total of eight studies were included in the mixed‐methods systematic review (two qualitative, two mixed‐methods and four quantitative studies). The students were satisfied with public health nursing simulation practices and had significant gains in the following activities: active learning, collaboration, critical thinking, teamwork, evaluating family and individual together, and practical communication skills. Conclusion The results of this review revealed that the experiences and gains of the nurses that they gain during their education process were essential, the numbers of simulation practices in the field of public health nursing were minimal, and they should be improved qualitatively.